Investigation of the effect of vascular endothelial growth factor gene 936 C/T polymorphism in familial Mediterranean fever patients - Yüce, Melek; Bağcı, Hasan (The European Research Journal, 2022)
Objectives: This study aims to investigate the effect of vascular endothelial growth factor (VEGF) gene 936C/T polymorphism (rs3025039) on the appearance of phenotypic characteristics of familial Mediterranean fever (FMF) patients that differ with respect to MEditerranean FeVer (MEFV) gene mutations. Here, we investigated a single functional polymorphism in the VEGF gene. Methods: The study group consisted of 223 FMF patients with definite diagnosis according to Tel-Hashomer criteria who carried MEFV gene mutations, while 208 FMF patients with definite diagnosis of FMF but without any mutations, making up the control group, were included in the study. The VEGF gene 936C/T polymorphism was genotyped using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Results: Genotype and allele frequencies of the VEGF rs3025039 polymorphism between the two groups were significantly different (p = 0.03 and p = 0.011, respectively). The TT genotype was found to be more frequent in the study group than in controls (4.9% vs. 3.3%, respectively). Conclusions: Our results seem to indicate that the VEGF 936C/T polymorphism affects the appearance of the phenotypic characteristics of FMF. It is possible that other variants of this gene may also have similar effects.